2021
DOI: 10.4103/jpbs.jpbs_376_21
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Stress in COVID Patient Post Treatment

Abstract: Aim: The purpose of our study was to examine the mental health status of patients with coronavirus disease-19 (COVID-19) who were hospitalized. Methodology: In this cross-sectional study, 106 inpatients with COVID-19 who had stable clinical conditions were evaluated psychologically by questionnaire: Depression, anxiety, and stress scales-21 (DASS-21). Results: About one-third of patients had comorbidities. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
1
Order By: Relevance
“…It was noted that only 12.9% of doctors and 7.4% of nurses experienced low-stress levels (Barczak et al, 2021). This is also in contradiction with other reports suggesting elevated stress levels in more than 90% of hospitalised patients (Kancherla et al, 2021), though other studies have indicated that elevated levels of perceived stress were observed in 40% of patients hospitalised with COVID-19 (Moseholm et al, 2022). The level of state anxiety in our hospitalised COVID-19 patients was comparable to the findings of previous studies, where low anxiety levels were present in about one-third of the people studied.…”
Section: Discussioncontrasting
confidence: 99%
“…It was noted that only 12.9% of doctors and 7.4% of nurses experienced low-stress levels (Barczak et al, 2021). This is also in contradiction with other reports suggesting elevated stress levels in more than 90% of hospitalised patients (Kancherla et al, 2021), though other studies have indicated that elevated levels of perceived stress were observed in 40% of patients hospitalised with COVID-19 (Moseholm et al, 2022). The level of state anxiety in our hospitalised COVID-19 patients was comparable to the findings of previous studies, where low anxiety levels were present in about one-third of the people studied.…”
Section: Discussioncontrasting
confidence: 99%